Modeling and control strategy of nuclear power plant based on heat pipe reactor and Brayton cycle system - Jian Wu; Wenxiang Gao; Mingjun Wang; Kailun Guo; Guanghui Su (Annals of Nuclear Energy, 2027)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

A high-accuracy stacking model for automatic identification of aeolian saltating tracks in high-speed pictures - Mengjie Pu; Fanmin Mei; Chuan Lin; Mingjun Sui; Hongda Chen; Shenyang He; Weikai Wang; Chang Zhou; Jin Su; Jinguang Chen (Aeolian Research, 2026)

SERPINB1 promotes porcine deltacoronavirus replication by targeting the viral accessory protein NS7a - Junfang Yan; Xinru Liu; Huixin Zhu; Liang Li; Hongye Pan; Renjie Bao; Qiutian Li; Jing Sun; Houhui Song; Mingjun Su (Veterinary Microbiology, 2026)

Revealing trapping effects of soil components on oil during the thermal desorption process of petroleum-contaminated soils - Haohao Bian; Shuaiyu Chen; Junhao Huang; Zixuan Zhang; Mingjun Wu; Wei Zhang; Sher Bahadar Khan; Xintai Su (Chemical Engineering Journal, 2026)

Development of a core streptavidin-bridging amplified ELISA based on p54 epitope for high-sensitivity detection of african swine fever virus antibodies - Jing Sun; Yingshan Zhou; Xingbo Liu; Xiaoxu Du; Jiongze Cheng; Huihua Zheng; Shuonan Pan; Junfang Yan; Xingdong Zhou; Xiaodu Wang; Zixiang Zhu; Dongbo Sun; et al. (The Veterinary Journal, 2025)

Elucidating the co-metabolism mechanism of 4-chlorophenol and 4-chloroaniline degradation by Rhodococcus through genomics and transcriptomics - Yonglin Bo; Yixue Niu; Mingjun Zhu; Yaru Wang; Yu Wang; Yuhua Su; Qiyou Liu; Gang Wang; Yongqiang Wang (Environmental Research, 2025)

Selection and validation of reference genes for the normalization of RT-qPCR gene expression data in Rheum tanguticum (Polygonaceae) under various abiotic stresses - Mingjun Yu; Jiarui Jin; Xiaoli Li; Yuping Liu; Xu Su; Marcos A. Caraballo-Ortiz; Penghui Zhang; Qian Yang; Rongju Qu; Zhaxi Cairang; Xuanlin Gao; Yinghui Zheng (Journal of Plant Physiology, 2025)

Analysis of the influence of bottom flow holes in control rod guide tubes on flow field and control rod displacement - Hanrui Qiu; Chuanming Zhang; Mingjun Wang; Wenxi Tian; G.H. Su (Annals of Nuclear Energy, 2025)

Steady-state thermal–hydraulic analysis of an NTP reactor core based on the porous medium approach - Zichao Han; Jing Zhang; Mingjun Wang; Wenxi Tian; Guanghui Su; Suizheng Qiu (Annals of Nuclear Energy, 2025)

Facile and green synthesis of Ag/Cu bimetallic nanoparticles using waste banana peel extract for effective corrosion inhibition of mixed sulfate-reducing bacteria - Yuhua Su; Fuli Wu; Peng Xiao; Hang Zhang; Guanglei Lv; Mingjun Zhu; Qiyou Liu; Chaocheng Zhao (Journal of Environmental Management, 2025)

Investigations of sodium droplet spreading and evaporation on surfaces with different wettability based on lattice Boltzmann simulations - Songsheng Tang; Kailun Guo; Ruibo Zhang; Mingjun Wang; Chenglong Wang; Xiaoqiang He; G.H. Su; Suizheng Qiu; Wenxi Tian (Annals of Nuclear Energy, 2024)

Numerical investigation on the effect of different factors on the flow-induced vibration of wire-wrapped fuel rod under axial flow - Hongjian Guo; Wei Li; Jing Zhang; Yingwei Wu; Pingting Jiang; Mingjun Wang; Suizheng Qiu; G.H. Su; Wenxi Tian (Annals of Nuclear Energy, 2024)

Exploration of the Formation Mechanism of Underground Brine Based on Hydrodynamic Environment Analysis Using Grain-Size Data of One Drilling Core - Qiao Su; Ying Yu; Mingjun Chen; Tengfei Fu; Wenzhe Lyu; Wenquan Liu (Journal of Marine Science and Engineering, 2024)
The Laizhou Bay area in China harbors a significant amount of Quaternary brine resources, which have been gradually depleted due to intensive long-term exploitation. It is widely accepted that underground Quaternary brine in Laizhou Bay originates from seawater. However, there are disputes regarding the specific form of seawater concentration and the geological processes leading to brine formation. Revealing the genesis of shallow brine in different geological environments is of great scientific significance for resource production and environmental protection. This study analyzed the hydrodynamic conditions of underground brine and adjacent strata based on grain size data, and the possible formation mechanisms of brine layers at different depths were discussed. The mineralization of underground brine is a complex process controlled by various factors, such as specific meteorological and paleogeographic environments, topography, and hydrogeological conditions. On the southern coast of Laizhou Bay, there are three ways in which underground brine layers are formed: residual evaporation from lagoons during the initial regression stage, the hypersaline zone in estuarine lagoons during high-sea-level periods, and brine formation from seawater evaporation on intertidal flats. Turbulent sea–land interactions and the development of river deltas are also necessary conditions for brine mineralization, as they are favorable for replenishing, transporting, and storing underground brine layers.

Assessment of groundwater quality of unconfined aquifers in an urbanized area using the water quality index method - Mingjun Zhu; Yueqing Xie; Jingjing Su; Shiang Lu (Environmental Science and Pollution Research, 2024)

Synergistic effects of mixed microorganisms on the corrosion of X65 carbon steel in actual reinjection water - Yuhua Su; Hang Zhang; Guanglei Lv; Fuli Wu; Peng Xiao; Mingjun Zhu; Chaocheng Zhao; Qiyou Liu (Journal of Environmental Chemical Engineering, 2024)

Biodegradation characteristics of p-Chloroaniline and the mechanism of co-metabolism with aniline by Pseudomonas sp. CA-1 - Mingjun Zhu; Yuhua Su; Yaru Wang; Yonglin Bo; Yufeng Sun; Qiyou Liu; Hang Zhang; Chaocheng Zhao; Yingying Gu (Bioresource Technology, 2024)

Study on flow regime prediction model for water-cooled reactor core based on machine learning algorithms - Yichao Ma; Dexiang Kong; Jing Zhang; Mingjun Wang; Wenxi Tian; Yingwei Wu; G.H. Su; Suizheng Qiu (Annals of Nuclear Energy, 2024)

Two parallel methods for the three-dimensional CFD coupling simulation of shell and tube heat exchangers - Shiqi Wang; Shaopeng He; Mingjun Wang; Wenxi Tian; G.H. Su; Suizheng Qiu (Annals of Nuclear Energy, 2024)

Performance evaluation of rhamnolipid biosurfactant produced by Pseudomonas aeruginosa and its effect on marine oil-spill remediation - Mingjun Zhu; Hang Zhang; Wu Cui; Yuhua Su; Shuo Sun; Chaocheng Zhao; Qiyou Liu (Archives of Microbiology, 2024)

Application of bacterial agent YH for remediation of pyrene-heavy metal co-pollution system: Efficiency, mechanism, and microbial response - Yuhua Su; Mingjun Zhu; Hang Zhang; Hongxu Chen; Jiguo Wang; Chaocheng Zhao; Qiyou Liu; Yingying Gu (Journal of Environmental Management, 2024)

Characteristic microbiome and synergistic mechanism by engineering agent MAB-1 to evaluate oil-contaminated soil biodegradation in different layer soil - Yaru Wang; Shuo Sun; Qiyou Liu; Yuhua Su; Hang Zhang; Mingjun Zhu; Fang Tang; Yingying Gu; Chaocheng Zhao (Environmental Science and Pollution Research, 2024)

Study on the characteristics of axial fluid excitation on fuel rods with spacer grids - Wei Li; Hongjian Guo; Jing Zhang; Yingwei Wu; Mingjun Wang; Suizheng Qiu; G.H. Su; Wenxi Tian (Annals of Nuclear Energy, 2023)

Analysis of flow-induced vibration of wire-wrapped fuel assemblies under the liquid metal axial flow in the Gen-IV nuclear reactor - Hongjian Guo; Wei Li; Jing Zhang; Yingwei Wu; Mingjun Wang; Suizheng Qiu; G.H. Su; Wenxi Tian (Annals of Nuclear Energy, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Experimental study on boiling two-phase of liquid sodium along a 7-rod bundle – Part Ⅰ: Pressure drop characteristics - Yandong Hou; Liu Wang; Kui Zhang; Mingjun Wang; Yingwei Wu; Wenxi Tian; Suizheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Experimental study on boiling two-phase of liquid sodium along a 7-rod bundle – Part Ⅱ: Heat transfer characteristics - Yandong Hou; Liu Wang; Kui Zhang; Mingjun Wang; Yingwei Wu; Wenxi Tian; Suizheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Bimetallic MOF synergy molecularly imprinted ratiometric electrochemical sensor based on MXene decorated with polythionine for ultra-sensitive sensing of catechol - Zhiwei Lu; Kai Wei; Hao Ma; Rongtao Duan; Mengmeng Sun; Ping Zou; Jiajian Yin; Xianxiang Wang; Yanying Wang; Chun Wu; Gehong Su; Mingjun Wu; et al. (Analytica Chimica Acta, 2023)

Nuclear thermal coupling optimization of baffled NTP reactor - Zimian Duan; Jing Zhang; Zichao Han; Mingjun Wang; Yingwei Wu; Yanan He; Wenxi Tian; Siuzheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Allopolyploidization facilitates gene flow and speciation among corn, Zea perennis and Tripsacum dactyloides - Muhammad Zafar Iqbal; Mingjun Cheng; Yuegui Su; Yang Li; Weiming Jiang; Huaxiong Li; Yanli Zhao; Xiaodong Wen; Lei Zhang; Asif Ali; Tingzhao Rong; Qilin Tang (Planta, 2019)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)